Pseudodifferential Local Interaction Equation for Moving Objects - Litovchenko, Vladyslav (Pleiades Publishing, 2022)
The general stochastic nature of the pseudodifferential superdiffusion equation is established. Developing Holtsmark’s idea, we show that the Green’s function of the Cauchy problem for this equation is the probability distribution of the local interaction force of moving objects in a system with power-law interaction